Electrodeposition of Cu-Sn alloys from a methanesulfonic acid electrolyte containing benzyl alcohol. (1st December 2017) - Bengoa, L.N.; Pary, P.; Conconi, M.S.; Egli, W.A.
Highlights: Cu-Sn alloys were readily deposited from a MSA-based electrolyte The proposed formulation allows deposition of coatings with up to 62.4 wt.% of Sn Addition of benzyl alcohol increases Sn content in the deposit at low Cu 2+ /Sn 2+ Benzyl alcohol also acts as a levelling agent avoiding rough or dendritic deposits Different phases can be deposited using this bath changing the deposition potential Abstract: Deposition of Cu-Sn alloys from a methanesulfonic acid electrolyte containing small amounts of benzyl alcohol was investigated. Polarisation experiments (cylic and linear sweep voltammetry) were carried out using a rotating disc electrode to identify the reduction and dissolution processes that take place in the system and to determine the effect of the solution constituents on them. Potentiostatic deposition was performed onto a rotating cylinder electrode and the resulting deposits were charactised using SEM and XRD. The results showed that co-deposition of copper and tin is possible even at potentials less cathodic than tin discharge potential. The latter was attributed to the underpotential deposition of Sn 2+ on a copper substrate. Smooth and compact deposits were obtained at various deposition potentials and Cu 2+ concentrations, with Sn contents between 1.6 - 62.4 wt.%. Several stable phases, such as pure copper, α -CuSn, ϵ -Cu3 Sn and η ′-Cu6 Sn5 phase, were detected at different operating conditions. Finally, it was found that BA increases the amount of tin in the deposit when Cu 2+ concentrations in the solution is kept low, especially at high overpotentials. This additive also inhibits the formation of dendrites and reduces surface roughness.